Oralidade e ensino: uma proposta de trabalho com o gênero oral público debate nas aulas de Língua Portuguesa - Rosa, Maria do Livramento Gomes (2020)
This research has as its theme the Orality and Teaching: a work proposal with public oral genre: debate in Portuguese Language classes. It was a work developed with ninth grade students of a public state elementary school in the city of Uberlândia/MG. We start from the question that the development of a work, focused specifically on the oral theme, which exposed here, can enable students to reflect on the language and the issues regarding orality. Thus, we propose as main objective: to investigate the applicability of the use of public oral in Portuguese Language classes and its relevance to broaden the argumentative power of students, through the analysis of the debate genre. Hence, we define as specific objectives: to study aspects related to orality: the notions of turn, discursive topic, voice quality, intonation, pauses and politeness; to verify what extent the use of public oral speech, manifested in the debate genre interferes with communicative competence. Besides that, to gather and elaborate material to support the teaching practice concerning the proper aspects of orality; to elaborate and analyze workshops with practices focused on the applicability of the public oral. Finally, to study the speech / writing relationship. Therefore, we chose to work with methodology of workshops, as it has an active character in which participants actively and reflexively appropriate the knowledge now presented in a practical way. After the application of workshops, we proceed to the analysis of the results present in the field notes of the research teacher, recordings of the debates and transcriptions. The analysis of the obtained data was made in the light of Marcuschi (1997,2001, 2003, 2007, 2008, 2008a, 2008b, 2008c), Bakhtin (2003), Dolz, Schneuwly and Haller (2013), Koch (1996, 2008) among others. The results showed that working with public oral genres is viable, especially with the debate genre, which proved to be an instrument capable of improving students' communicative competence in formal contexts. In view of that, it becomes urgent a work, which focuses on oral genres in Portuguese language classes, so that the speaking and writing to be seen from the same value position, increasing the effectiveness of our practices.